OUTCOME OF SURGICAL MANAGEMENT OF BIMALLEOLAR FRACTURES IN ADULTS - VEM, KRISHNA BHARGAVA; Kondlapudi, Anvesh Kumar; Murari, SaiPavan Kumar; Murthy D, Srinivasa (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: Appropriate management of malleolar injuries is crucial as the ankle is an important weight-bearing joint, and locomotion is determined by and dependent on joint stability. We studied the functional outcome of surgically managed bimalleolar fractures of the ankle. Methods: Fractures were classified anatomically and as per Laugeâ€“Hansen, arbeitsgemeinschaft fÃ¼r osteosynthesefragen (AO)/orthopedic trauma association classification. The stability of the structures at the fracture site, the extent of damage, mechanism of injury was assessed. Radiologically, tibiofibular clear space of >6 mm and widening of the medial clear space of >4 mm were indicators of syndesmotic instability. All underwent open reduction and internal fixation under spinal and/epidural anesthesia. We used tension band wiring, malleolar screw, Kirschner wires (K-wires), cancellous screws for fixing medial malleolus; one-third tubular plate and K-wires for lateral malleolus. Patients were followed up at 6 weeks for 6 months, evaluated using Biard and Jackson’s ankle scoring system. Results: Of 30 patients, 25 (83.3%) were men. The right ankle was involved in 56.6%. Road traffic accident was the cause in 83.3%. 14 (46.6%) had supination external rotation injuries. The AO Type B was the most common (66.6%). All had a complete union, with a mean time for union 10.6 weeks (8-14 weeks). Functional scores were categorized into excellent (60%), good (26.6%), fair and poor (n=02 each). Superficial and deep infection (n=02 each), delayed union (n=01) were the complications. Conclusion: ORIF restores the articular congruity of the ankle joint. Cancellous or malleolar screws are better for fixation of the medial malleolus and lateral plating for fibular fractures.